Agenda-setting y percepciones sobre el VIH/ Sida en poblaciones universitarias limeñas: la gran influencia de la información periodística - Cristobal Ponce, Irene (2008)
This work presents within the framework of a mediatically starred scenario, the influence of VIH/Sida news coverage from Limean newspapers on the agenda and the perceptions of both male and female young students of a public university. In the first place, the agenda setting function about the Limean newspaper influence over the university students will be studied. This will be done to know the process of transference of issue salience of the media agenda to the public agenda, moreover to how the frecuency of VIH/Sida ítems published by the newspapers influences the students. However, the influence of the media is larger. In second place, it will be studied the influence over the perceptions’: about the gravity of the infection by VIH/Sida and then, about the risk of getting this condition.